Mining and the development of local communities an analysis of the impact of large-scale mining activities to poverty reduction using remotely sensed data - Magpayo, Camille Angela A. (School of Economics, University of the Philippines Diliman, 2019)
The externalities associated with mining in the Philippines have long been a subject of interest to social scientists and legislators to assess the level of impact of existing laws and policies on the development of communities surrounding the mineral extraction sites. However, due to the limited availability of data, previous studies in the Philippines have either evaluated the effects of mining on the welfare of employees of mining companies, or have closely examined the impact of chosen mining sites on the natural and human environments. This study aims to investigate the causal effects of mining to community development using Generalized Synthetic Control Method (GSCM) and remotely_sensed data of nighttime lights as indicators of national growth and This paper finds that the contribution of the mining industry to economic development is miniscule and that affected municipalities have remained in poverty even years after the establishment of the mining sites.